Effect of adding onion oil and seeds to local goose diet on the levels of antioxidants and sex hormones. - Nashwan Majeed Ali (Aceh Journal of Animal Science, 2022)
This study was conducted in the scientific research field of the Technical Institute / Shatrah for the period from 3/1/2018 to 3/5/2018 to know the effect of adding different levels of onion oil and seeds to Iraqi local goose rations on some antioxidants and levels of sex hormones, as it was used in This study: 75 sexually mature female geese, and at the beginning of the production stage, were divided into five treatments, and for each treatment 15 females divided into three replicates / each replicate had 5 females. The experimental treatments were as follows: The first treatment (T1) was a control treatment without any addition, the second treatment (T2) was added to onion seed powder at an amount of 1.5 gm per kg of feed, the third treatment (T3) was added to onion seed powder at an amount of 3 gm per kg of feed, The fourth treatment (T4) was added to onion seed oil at an average of 0.10 ml per kg of feed, while the fifth treatment (T5) was added to it onion seed oil at an average of 0.20 ml per kg of feed and these percentages were added from the beginning of the experiment until the end of the experiment period. Blood was drawn from the experimental birds from the jugular vein weekly for the purpose of measuring the concentrations of MDA and SOD and the level of the hormones Progesterone and Estrogen and then according to an average every three weeks to present the results of the study on the basis of six periods of length, each of 21 days, the results of the study indicated a decrease Significant in the oxidative enzyme activity understudy in the addition treatments compared to the control treatment, also the sex hormones took the same curve of significant improvement of the additional treatments compared to the control treatment.